Teaching Public Law: Content, Context and Coherence - Graeme Orr (Legal Education Review)
This volume of the Review, Volume 25, is as usual made up two issues, a General Issue and a Special Issue. The Special Issue contains three articles about the teaching of public law, and is introduced by a separate Foreword written by guest editors Gabrielle Appleby, Alexander Reilly and Sean Brennan. The General Issue is comprised of twelve articles that explore a variety of legal education topics, and is the focus of this Foreword.